Hududnama by čiftluk Kizlaraga Mustapha from 1591 on which Mrkonjić-grad was founded (Prilozi za orijentalnu filologiju, 2017)
It is well known that, in accordance with Sheriat Law, a vakif (an endowment for charitable purposes) could only be created from personal goods/wealth, regardless of whether those goods were inherited, bought or given by the Sultan (in the latter case a document concerning the donation was issued). Before a vakifname (endowment charter) was drawn up, the competent Sheriat court had to confirm that the person who wanted to make an endowment was the real owner of the goods in question. If the founder of a vakf wanted to endow a plot of land, the court had to confirm and quote the precise borders of the property.This paper gives the original text and a Serbo-Croat translation of the »hududname« (a document certifying the precise boundaries of a fi/tlik) of a senior imperial official at the court in Istanbul, Hadži Mustafa, son of Mehmedbeg and Aiše hatun, who was born in the village of Gornja Kloka (probably in the first half of the 16th century). This village is present-day Mrkonjić Grad (in Bosnia) and the endowment laid the foundations for the town known as Yaytse Yenice (Novo Jajce) which was later to become Varcar Vakuf and, finally, in 1924, to be renamed Mrkonjić Grad. The hududname giving the precise boundaries of the vakf, was issued by the Jajce kadi, Mustafa, son of Yusuf, after an on the spot investigation by a commission. The document goes into great detail about how 29 distinguished persons took part in the investigation between 6 th and 16th Feb. 1591, i.e. four years before the drawing up and legalisation of the vakifname in Istanbul between 11th and 20th Feb. 1595. Kizlaraga Mustafa's vakfname, or more precisely a photocopy of a certified copy of the vakfname .(1591) is kept in Gazi Husrevbeg library, index no. 263. According to this authorised copy, the vakfname has been prepared for publication in a special book of dating 16th-century vakfnames which will be published by the Sarajevo Oriental Institute.